Studi faktor-faktor yang mempengaruhi profitabilitas bank umum syariah di indonesia - Almunawwaroh, Medina (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The study was conducted to determine how the effect of CAR, NPF, and FDR on ROA. During the observation period, the research data proved to be normally distributed. Based on the normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test, there were no variables that deviated from the classical assumption. Based on this, the research data has met the requirements to use the multiple linear regression model. The results of this study indicate that CAR has an insignificant positive effect on ROA, NPF has a significant negative effect on ROA, and FDR has an insignificant positive effect on ROA. The predictability of the three independent variables on ROA in this study was 89%, the difference of 11% was caused by other factors that were not included in the research model.